PEMANFAATAN LIMBAH CANGKANG TELUR AYAM SEBAGAI ADSORBEN PADA PEMURNIAN GLISEROL DENGAN METODE ASIDIFIKASI DAN ADSORPSI - Sandro Nadeak, Jesica Mentari Hasibuan, Lies Widya Naibaho, Mersi Suriani Sinaga (Jurnal Teknik Kimia USU, 2019)
Glycerol as a byproduct of biodiesel production was approximately formed 10-20% of the biodiesel weight. Impurities which contained in the glycerol such as inorganic salts, catalysts, water and matter organic non glycerol (MONG) which contained free fatty acids, fatty acids as residual of methyl ester, glycerides, and alcohols (generally methanol or ethanol) had a significant effect on glycerol concentration. We needed some treatment, especially to eliminate the impuritis. This study aims to purify glycerol by acidfication using phosphate and adsorption with chicken egg shell waste. This research was begun with the pretreatment of glycerol using phosphoric acid with the variable of test weight ratio (w/w) acid added 1: 0.2; 1: 0.4; 1: 0.6; 1: 0.8 and 1: 1 , continued with adsorption using thermally activated chicken egg shell waste with the variable weight percent adsorbent (%w/w) 3%, 6%, 9%, 12% and 15% with reaction conditions, stirring speed 250 rpm and adsorption time 120 minutes. The purest result was obtained at weight ratio (w/w) acidification of 1: 0.6, weight percent adsorbent (% w/w) 15% with glycerol content of 67.22%, density 1.171 g / cm3, moisture content 2.796%, ash content 13.852% and MONG content 16.130%.